The White Paper - An Analysis
1944-03 1944 1940s 12 pages 11 WHITE PAPER. 45. Instead of integrating the various branches of practice in a single service, the proposed administrative structure appears to contemplate the division of the profession into at least four groups— (1) Consultants and Specialists, under the control of the Joint Health Authority, but appointed by individual hospital authorities, voluntary and municipal ; (2) General practitioners in separate practice, under the control of the Central Medical Board ; (3) General practitioners in health centre practice appointed by and under the joint control of local authorities and the Central Medical Board ; (4) The Public Health Service, appointed by and under the control of local authorities. 46. The service is designated a comprehensive service for all and its aim is to make available all necessary forms of health care for all people in England, Scotland and Wales. The White Paper comments :— 47. "This cannot all be performed at a stroke of the pen, on an appointed day ; but nothing less than this must be the object in view, and the framing of the service from the outset must be such as to make it possible. For some time some aspects of the new service will be less complete than could be wished ..." 48. A full service in dentistry and opthhalmology are instanced as examples of temporary exceptions to the comprehensiveness of the plan. And although detailed proposals for the consultant service remain for later consideration there is no suggestion in the Paper that a general practitioner service may be put into operation without corresponding arrangements for other branches of practice. (Interim Proposals.) PRINCIPLE L. Pending the consideration and completion of the foundation administrative changes mentioned in Principle J above, as a step towards the satisfaction of Assumption B, there should be extension of National Health Insurance to include dependants of insured persons and others of like economic status and to cover consultant and specialist services and laboratory and hospital facilities as well as general practitioner service. The service should be improved from time to time as recommended by the profession. Those persons with incomes above an agreed limit could, if Parliament decided to make the service avaiable [available] to every member of the community, be permitted to become voluntary contributors to the extended service. A reconstruction of Insurance Committees would be necessary. WHITE PAPER. 49. The White Paper is not stated to be an interim plan. There is no intimation that the government intends to undertake or initiate an examination of the local authority structure generally. PRINCIPLE M. There should be initiated, by arrangement and agreement between the Government and the profession, organised experiments in the methods of practice such as group practice, including health centres of different kinds, which should extend to general practitioner hospital units attached to general hospitals. Future developments in group practice should depend upon the results of such clinical and administrative experimentation. WHITE PAPER. 50. The following extract from the White Paper is relevant :— "The Government fully agree that grouped practices, to which numerous privately arranged partnerships are already pointing the way, must have a high place in the planning of the new service and they are designing the service with this constantly in view. Yet the conception of grouped practices cannot represent the whole shape of the future service. In the first place, there has not yet been enough experience of the idea translated into fact. Not enough has been found out, by trial and error, to determine the conditions under which individual doctors can best collaborate or even the extent to which in the long run the public will prefer the group system. Second, it is certain that the system could not be adopted everywhere simultaneously. The change, if experience shows that it should be complete, will take time. The Government intend, therefore, that the new service shall be based on a combination of grouped practice and of separate practice side by side. They propose to place the group idea in the forefront of their plans in order that there may be a full trial on a large scale of the working arrangements of this kind. Grouped practices are more likely to be found suitable in densely populated and highly built-up areas and it is there particularly (though not exclusively) that they should first be tried. It will then be possible to watch the development, with the medical profession, and to decide in the light of experience how far and how fast a changeover to the new form of practice can and should be made." 51. At first sight it might appear that the Government intends that a period of experiment should precede the adoption of any general type or types of health centre. Viewed as a whole the Paper does not confirm this impression. At its worst the joint health authority, after consulting the local health services council (taking or not taking its advice) can submit to the Minister a plan for the establishment of health centres. The Minister, having consulted or not having consulted the central health services council, or having consulted it (either taking or not taking its advice) can approve the plan. Thereafter the county and county borough councils put it into operation. There is no particular feature of this arrangement which ensures that there shall be experiment. Indeed, unless there is a central body — the central, health services council or other — established for the purpose of planning and co-ordinating the 21/570